Transcendent Unity and Social Transformation: A Comprehensive Analysis of Swami Vivekananda’s Philosophical Legacy and Contemporary Relevance - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This scholarly paper presents a critical analysis of Swami Vivekananda (1863-1902) as a pivotal figure in the development of modern Hindu thought and intercultural religious dialogue. Drawing upon extensive archival research and contemporary theoretical frameworks, this study examines Vivekananda's philosophical synthesis through the lens of what I term "transformative neo-Vedanta": a dynamic reinterpretation of traditional metaphysics that enables both spiritual inquiry and social engagement. The paper contextualizes Vivekananda within the broader Indian Renaissance movement while analyzing his distinctive contributions to religious pluralism, educational philosophy, and national identity formation. Through careful examination of primary texts and historical reception, I argue that Vivekananda's philosophical framework represents not merely a revival of ancient wisdom but a creative reconstruction that responds to modernity's challenges while preserving the experiential core of Vedantic spirituality. This study reveals how Vivekananda's vision continues to offer substantive resources for addressing contemporary tensions between religious particularity and universal ethics, contemplative practice and social action, and cultural rootedness and global engagement.